γ-Aminobutyric Acid (GABA) Priming Improves Seed Germination and Seedling Stress Tolerance Associated With Enhanced Antioxidant Metabolism, DREB Expression, and Dehydrin Accumulation in White Clover Under Water Stress - Zhou, Min; Hassan, Muhammad Jawad; Peng, Yan; Liu, Lin; Liu, Wei; Zhang, Yan; Li, Zhou (Frontiers in Plant Science, 2021)
As an important plant growth regulator, the role of γ-aminobutyric acid (GABA) in regulating seed germination has never been elucidated under drought stress. The present study was conducted to investigate the impact of GABA pretreatment on seeds germination of white clover (Trifolium repens) under water deficient condition. Results demonstrated that seeds pretreated with 2 μmol/L GABA significantly alleviated decreases in endogenous GABA content, germination rate, germination potential, germination index, root length, and fresh weight along with marked reduction in mean germination time after 7 days of germination under drought stress. In addition, seeds priming with GABA significantly increased the accumulation of soluble sugars, non-enzymatic antioxidants (reduced ascorbate, dehydroascorbic acid, oxidized glutathione, and reduced glutathione), and enzymes (superoxide dismutase, peroxidase, catalase, ascorbate peroxidase, dehydroascorbate reductase, glutathione reductase and monodehydroasorbate reductase) activities involved in antioxidant metabolism, which could be associated with significant reduction in osmotic potential and the accumulation of superoxide anion, hydrogen peroxide, electrical leakage and malondialdehyde in seeds under drought stress. The GABA-pretreated seeds exhibited significantly higher abundance of dehydrin (DHN, 56 KDa) and expression levels of DHNs encoding genes (SK2, Y2K, Y2SK and Dehydrin b) and transcription factors (DREB2, DREB3, DREB4 and DREB5) than the untreated seeds during germination under water-limited condition. These results indicated that the GABA regulated improvement in seeds germination associated with enhancement in osmotic adjustment, antioxidant metabolism, and DREB-related DHNs expression. Current study will provide a better insight about the GABA-regulated defense mechanism during seeds germination under water-limited condition.